Hubungan Perilaku Hygiene dengan Infeksi Soil Transmitted Helminth pada Balita di Wilayah Kerja Puskesmas Bandarharjo Kota Semarang - Rachmawati, Aulia Noor; Sutiningsih, Dwi; Martini, Martini (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background : The prevalence of STH in Central Java reached 33.8%, with Ascaris lumbricoides found in toddlers living in areas with poor sanitation. The Bandarharjo Community Health Center is one of the community health centers in Semarang City that serves coastal areas. The objective of this study was to determine the correlation between STH infection and personal hygiene in children under five years of age at the Bandarharjo Community Health Center in Semarang.Methods : This was an observational study using the cross-sectional design. A total of 150 subject were obtained from children under five years in the field area of Bandarharjo Primary Healthcare. STH examination was conducted through kato-katz method, while the personal hygiene was observing by diung an interview to the children parents. Statistic analyzed used Chi-Square test.Result: The prevalence of soil-transmitted helminths (STH) in the Bandarharjo Community Health Center working area reached 82.6%, with hookworm and Ascaris lumbricoides due to poor sanitation. There is a correlation between the habit of wearing sandals and washing hands with soap and STH infection (p-value > 0.000) & (p-value > 0.038). Respondents who did not wash their hands with soap and wore sandals were 5.6 and 2.44 times more likely to be infected, respectively.Conclusion: Poor personal hygiene can increase the risk of STH infection in children under five years of age. Therefore, parents have a role to play in teaching, educating, and accustoming children to always practice healthy behaviors.